Developing innovative and effective marketing strategies to deepen customer engagement and expand market reach successfully - Masih, Ni Ketut; Pemayun, I Dewa Gede Ari; Sinaga, Firman (Journal of Commerce, Management, and Tourism Studies, 2025)
This study investigates effective marketing strategies for AUTO2000, with the goal of increasing sales volume during the Covid-19 pandemic. Utilizing a descriptive research approach, data were collected through observation, interviews, and document analysis. The findings demonstrate that applying segmentation, targeting, and positioning (STP) strategies contributes to improving sales performance. Specifically, the company can benefit from a differentiated targeting strategy, which involves focusing on multiple potential market segments. Additionally, a positioning strategy based on attributes and product categories allows the company to concentrate on key products that resonate with target markets. The results suggest that AUTO2000's product diversity, coupled with innovative offerings, aligns well with these strategies. The study concludes that continuous adaptation of marketing strategies, paired with creative solutions, is essential for meeting sales targets, particularly in challenging periods such as the pandemic.